2006
DOI: 10.1037/0278-7393.32.3.559
|View full text |Cite
|
Sign up to set email alerts
|

The negated conditional: A litmus test for the suppositional conditional?

Abstract: Under the suppositional account of conditionals, when people think about a conditional assertion, "if p then q," they engage in a mental simulation in which they imagine p holds and evaluate the probability that q holds under this supposition. One implication of this account is that belief in a conditional equates to conditional probability [P(q/p)]. In this paper, the authors examine a further implication of this analysis with respect to the wide-scope negation of conditional assertions, "it is not the case t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 22 publications
9
76
2
Order By: Relevance
“…Previous studies have demonstrated their occurrence, but they have tended to rely on conditionals of the form if A then B (Johnson-Laird & Savary, 1999). The meanings of conditionals are controversial, and critics have argued that the illusory conclusions are, in fact, valid (Handley, Evans, & Thompson, 2006;Rips, 1997;Stenning & van Lambalgen, 2008). Although we do not accept this argument, in our present study, we used novel instances of illusory inferences that are simpler than those previously studied and that use connectives with uncontroversial meanings, such as disjunctions and conjunctions.…”
Section: Memory Full Server Busymentioning
confidence: 99%
“…Previous studies have demonstrated their occurrence, but they have tended to rely on conditionals of the form if A then B (Johnson-Laird & Savary, 1999). The meanings of conditionals are controversial, and critics have argued that the illusory conclusions are, in fact, valid (Handley, Evans, & Thompson, 2006;Rips, 1997;Stenning & van Lambalgen, 2008). Although we do not accept this argument, in our present study, we used novel instances of illusory inferences that are simpler than those previously studied and that use connectives with uncontroversial meanings, such as disjunctions and conjunctions.…”
Section: Memory Full Server Busymentioning
confidence: 99%
“…For this sort of conditional, unlike the specific conditionals used in the present experiments, there is no clear-cut way to determine the conditional probability of the consequent given the antecedent and no directly relevant frequency data that can be brought to bear to determine this conditional probability. Perhaps largely as a result of this, past research that has examined how people judge the probability of conditionals has eschewed examining such conditionals about truly unique events, favoring conditionals that are amenable to the presentation of relevant probabilistic evidence (see, e.g., Handley et al, 2006;Oberauer et al, 2007;Oberauer & Wilhelm, 2003; although see Douven & Verbrugge, 2012;Over et al, 2007, for relevant exceptions).…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Studies that have asked for assessments of degree of belief in conditional assertions or of the probability of conditional assertions appear to have generally favored Evans et al's (2003) conditional probability hypothesis by showing that individuals' judgment of the probability that a conditional statement is true declines roughly linearly as a function of the conditional probability of the consequent given the antecedent (e.g., Evans et al, 2003Evans et al, , 2007Handley et al, 2006;Oberauer et al, 2007;Oberauer & Wilhelm, 2003;; although for countervailing argument and evidence, see also Girotto & Johnson-Laird, 2004;Johnson-Laird, 2011).…”
Section: Relation To Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes they appear to deny it as ¬(p -> q), but other times they seem to deny it as p -> ¬q. This problem has been studied in many works and papers (HANDLEY; EVANS; THOMPSON, 2006;). Even Khemlani, Orenes and Johnson-Laird (2014) analyzes it as well.…”
Section: And ¬(P · Q)mentioning
confidence: 99%